SISTEM INFORMASI AKADEMIK SEKOLAH DASAR SWASTA CERDAS MEDAN BERBASIS WEB - Novita Sari Br Tarigan; Denny H. S. Maha (UPPM, 2019)
The progress of information technology today has provided great benefits in the world ofeducation, the construction of school website and the development of computer based academicinformation systems is part of the utilization of information technology allows academic data canbe processed quickly and easily so that the presentation of the required academic informationreports can be obtained precisely quickly and efficiently. the purpose of this system is to overcromethe problems that exist has the old system that has been running by creating an intelligent fieldeducation academic information system.